Reverse genetic analysis of yeast YPR099C/MRPL51 reveals a critical role of both overlapping ORFs in respiratory growth and MRPL51 in mitochondrial DNA maintenance. Issue 6 (2nd August 2019) - Sahu, Pushpendra Kumar; Salim, Sagar; PP, Mubthasima; Chauhan, Sakshi; Tomar, Raghuvir Singh
ABSTRACT: The Saccharomyces cerevisiae genome contains 6572 ORFs, of which 680 ORFs are classified as dubious ORFs. A dubious ORF is a small, noncoding, nonconserved ORF that overlaps with another ORF of the complementary strand. Our study characterizes a dubious/nondubious ORF pair, YPR099C / MRPL51, and shows the transcript and protein level expression of YPR099C . Its subcellular localization was observed in the mitochondria. The overlapping ORF, MRPL51, encodes a mitochondrial ribosomal protein of large subunit. Deletion of any ORF from YPR099C / MRPL51 pair induces common phenotypes, i.e. loss of mtDNA, lack of mitochondrial fusion and lack of respiratory growth, due to the double deletion ( ypr099c Δ/Δ mrpl51 Δ/Δ) caused by sequence overlap. Hence, we created the single deletions of each ORF of the YPR099C / MRPL51 pair by an alternative approach to distinguish their phenotypes and identify the specific functions. Both the ORFs were found essential for the functional mitochondria and respiratory growth, but MRPL51 showed its specific requirement in mtDNA stability. The mechanism of mtDNA maintenance by Mrpl51 is probably Mhr1 dependent that physically interacts with Mrpl51 and also regulates mtDNA repair. Overall, our study provides strong evidence for the protein level expression of a dubious ORF YPR099C and the bifunctional role of Mrpl51 in mtDNA maintenance. Abstract : YPR099C is required in respiratory growth whereas MRPL51 regulates mtDNA maintenance in addition to respiratory cell growth.